Clinical results of a surgical technique using endobuttons for complete tendon tear of pectoralis major muscle: report of five cases - Uchiyama Yoshiyasu; Miyazaki Seiji; Tamaki Tetsuro; Shimpuku Eiji; Handa Akiyoshi; Omi Hiroko; Mochida Joji (BMC, 2011)
Abstract Background We herein describe a surgical technique for the repair of complete tear of the pectoralis major (PM) tendon using endobuttons to strengthen initial fixation. Methods Five male patients (3 judo players, 1 martial arts player, and 1 body builder) were treated within 2 weeks of sustaining complete tear of the PM tendon. Average age at surgery and follow-up period were 28.4 years (range, 23-33) and 28.8 months (range, 24-36). A rectangular bone trough (about 1 × 4 cm) was created on the humerus at the insertion of the distal PM tendon. The tendon stump was introduced into this trough, and fixed to the reverse side of the humeral cortex using endobuttons and non-absorbable suture. Clinical assessment of re-tear was examined by MRI. Shoulder range of motion (ROM), outcome of treatment, and isometric power were measured at final follow-up. Results There were no clinical re-tears, and MRI findings also showed continuity of the PM tendon in all cases at final follow-up. Average ROM did not differ significantly between the affected and unaffected shoulders. The clinical outcomes at final follow-up were excellent (4/5 cases) or good (1/5). In addition, postoperative isometric power in horizontal flexion of the affected shoulder showed complete recovery when compared with the unaffected side. Conclusions Satisfactory outcomes could be obtained when surgery using the endobutton technique was performed within 2 weeks after complete tear of the PM tendon. Therefore, our new technique appears promising as a useful method to treat complete tear of the PM tendon.